Is there a "Scottish effect" for self reports of health? Individual level analysis of the 2001 UK census - Popham Frank (BMC, 2006)
Abstract Background Scotland's overall health record is comparatively poor for a Western European country, particularly amongst people of working age. A number of previous studies have explored why this might be the case by comparing mortality in Scotland with England and Wales. A study in the 1980s showed that the higher prevalence of deprivation in Scotland accounted for Scotland's excess mortality risk. However, more recent studies suggest that deprivation now explains less of this excess. This has led to the suggestion that there is a yet unidentified "Scottish effect" contributing to Scotland's mortality excess. Recent research has also suggested that there could be an unidentified effect influencing Scotland's higher rate of heart disease. This paper explores whether there is also an unexplained Scottish excess, relative to England, in self reports of poor health. Methods Data came from the individual Sample of Anonymised Records, a 3% random sample of the 2001 UK census. Using logistic regression models, self reports of health (limiting illness and general health) from the working age populations (aged 25 to 64) of Scotland and England were compared. Account was taken of people's country of birth. Stratified analysis by employment status allowed further exploration of Scotland's excess. Results People born and living in Scotland reported higher levels of poor general health and limiting illness compared to people born and living in England. Adjustment for socioeconomic position and employment status largely explained the higher rates. In the stratified analysis a Scottish excess was seen only amongst the economically inactive born and living in Scotland. For those in employment, people born and living in Scotland actually had slightly lower odds of reporting poor general health and limiting illness than people born and living in England. Conclusion This analysis suggests that higher rates of poor self reported health in Scotland can be explained by differences in employment and socioeconomic position and so there is unlikely to be an unidentified "Scottish effect" for self reports of health. Scotland's excess of poor general health and limiting illness amongst the economically inactive is probably attributable to its economic and employment history.